Organization of physical education classes in special medical groups under digitalization conditions - Lyashko, G.I.; Grigan, S.A. (Theory and Practice of Physical Culture, 2026)
The current stage of higher education development is characterized by a profound transformation of the goals, content, and technologies of the educational process, driven by both global socio-economic changes and the rapid development of digital technologies. This process acquires particular significance in the field of physical education of students, traditionally focused on face-to-face interaction, practical motor activity, and direct pedagogical control. Objective of the study is to determine the effectiveness of special medical group classes under the conditions of digitalization of the university’s physical education system. Methods and structure of the study. The experiment involved 36 students from a special medical group, divided into experimental and control groups. Classes in the experimental group are organized on the basis of a structural-functional model integrating traditional means of Adapted Physical Culture (APC) and digital educational technologies; during the classes, digital monitoring tools for physical activity and functional state of students are used, providing objective control and individualization of motor loads; systematic pedagogical support for students with health limitations is ensured using digital feedback channels; the content of classes is adapted to the individual psychophysical capabilities of students and implemented in face-to-face, distance, and blended formats; elements of self-control and self-regulation of students’ motor activity are purposefully incorporated into the educational process. Results and conclusions. The results obtained during the experiment allow us to conclude that the introduction of digital tools into the process of organizing classes creates additional pedagogical conditions for increasing the effectiveness of the body’s adaptive responses.